Synthesis of a new class of naphthoquinone glycoconjugates and evaluation of their potential as antitumoral agents. Issue 116 (9th November 2015) - Campos, Vinicius R.; Cunha, Anna C.; Silva, Wanderson A.; Ferreira, Vitor F.; Santos de Sousa, Carla; Fernandes, Patrícia D.; Moreira, Vinícius N.; da Rocha, David R.; Dias, Flaviana R. F.; Montenegro, Raquel C.; de Souza, Maria C. B. V.; Boechat, Fernanda da C. S.; et al.
Abstract : A novel series of carbohydrate-based naphthoquinones was synthesized and evaluated for cytotoxicity against different human cancer cell lines (HCT-116, A-549 and MDA-MB 435). The compounds derived from juglone showed better cytotoxicity profiles. Abstract : A novel series of carbohydrate-based naphthoquinones was synthesized and evaluated for cytotoxicity against different cancer cell lines. The compounds derived from 5-hydroxy-1, 4-naphthoquinone (juglone) showed better cytotoxicity profiles against HCT-116, A-549 and MDA-MB 435 human cancer cells than the parent compound. The results suggest that the hydroxyl group on the aromatic ring increased the pro-oxidant activity of these new naphthoquinone derivatives. Furthermore, two derivatives were found to be more active against melanoma cells (MDA-MB435) than the clinically useful anticancer agent doxorubicin, and none of the compounds caused mouse erythrocyte lysis.